A re‐examination of antidepressant treatment‐emergent mania in bipolar disorders: evidence of gender differences. (1st April 2017) - Scott, J.; Brichant‐Petitjean, C.; Etain, B.; Henry, C.; Kahn, J.‐P.; Azorin, J.‐M.; Leboyer, M.; Bellivier, F.
Abstract : Objective: To explore the prevalence and clinical profile of males and females who develop antidepressant treatment‐emergent mania (ATEM). Method: From an original sample of 754 patients with BD, we identified ATEM+ cases ( n = 75) and ATEM‐ controls ( n = 135) that met stringent criteria. We specifically examined the combinations of clinical factors that best classified males and females as ATEM+ cases. Results: Seventy‐five individuals were classified as ATEM+; 87% of ATEM events occurred during antidepressant monotherapy. Regression analyses demonstrated that the presence of an alcohol and/or substance use disorder [Odds Ratio (OR) 6.37], a history of one or more suicide attempts (OR 4.19) and higher number of depressive episodes per year of illness (OR 1.71) correctly classified 73% of males. In contrast, 84% of females were correctly classified on the basis of a positive history of thyroid disorder (OR 3.23), a positive family history of BD I (OR 2.68) and depressive onset polarity (OR 2.01). Conclusion: Using stringent definitions of ATEM status to reduce the probability of inclusion of false‐positive cases and false‐negative controls, we identified for the first time that the risk profiles for the development of an ATEM differ significantly according to gender.